EAES Guidelines for Endoscopic Surgery Twelve Years Evidence-Based Surgery in Europe - Neugebauer, Edmund A. M.; Sauerland, Stefan; Fingerhut, Abe; Millat, Bertrand; Buess, Gerhard F. (Springer Berlin Heidelberg : Imprint: Springer, 2006)
Leading European laparoscopic surgeons have compiled the recommendations of the European Association for Endoscopic Surgery (EAES) in this book. All statements are based not only on the experts' opinions, but also on a formal assessment of the scientific literature. This work allows readers to gain an overview of cutting edge surgical research. All recommendations describe exactly the proven benefit of each surgical procedure and technique. Most guidelines contain key statements. All chapters follow a structured format to allow quick identification of all recommendations. In summary, this work provides a perfect overview of the achievements in laparoscopic surgery throughout the last decade.